Developing Students’ Religious Character Through Islamic Religious Education Learning - Chintya Sari; Septi Rahayu; Heny Friantary; Yosi Yulizah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study examines the implementation of Islamic Religious Education learning in developing students’ religious character. The research aims to analyze the learning process, identify supporting and inhibiting factors, and describe the role of Islamic Religious Education in strengthening students’ moral and spiritual values within the school environment. A qualitative descriptive approach was employed to obtain comprehensive data related to the implementation of religious character education. Data were collected through classroom observations, interviews with teachers and students, and documentation studies concerning school programs and learning activities. The findings reveal that Islamic Religious Education learning contributes significantly to the development of students’ religious character through the application of habituation methods, role modeling, guidance, and motivational approaches. Religious activities integrated into school culture strengthen students’ discipline, honesty, responsibility, tolerance, and spiritual awareness. Supporting factors include teacher involvement, positive school culture, parental support, students’ motivation, and adequate educational facilities. Inhibiting factors include negative social influences, excessive use of digital media, differences in family backgrounds, and limited student self-discipline. The study concludes that the successful development of students’ religious character requires continuous cooperation among schools, teachers, parents, and communities in implementing consistent Islamic value education within students’ daily lives.